Comparative Effectiveness of Novel Oral Anticoagulants in Obese Patients with Atrial Fibrillation - Shah, Islam; Zahra, Atya; Ahmad, Munir; Aabid , Javeria; Ahmed, Hamdy Abdelfattah (Journal of Neonatal Surgery, 2024)
Background: Atrial fibrillation (AF) is a leading cause of stroke worldwide, and obesity is a recognized risk factor that may influence the pharmacokinetics of anticoagulants. The optimal choice of novel oral anticoagulant (NOAC) for obese AF patients remains uncertain, with limited comparative data available. Methodology: This prospective observational study was conducted from March 2023 to March 2024, enrolling 72 obese patients (BMI ≥ 30 kg/m²) with non-valvular AF. Participants were divided into four groups according to the NOAC prescribed: Apixaban, Rivaroxaban, Dabigatran, or Edoxaban. Baseline demographic data, comorbidities, CHA₂DS₂-VASc and HAS-BLED scores were recorded. Patients were followed for 12 months ‘to evaluate effectiveness outcomes (stroke/systemic embolism, AF-related hospitalization, all-cause mortality) and safety outcomes (major bleeding, gastrointestinal bleeding, intracranial hemorrhage, discontinuation due to adverse events)’. Results: Apixaban users had ‘the lowest rate of stroke/systemic embolism (5.6%) and major bleeding’ (5.6%) compared with Rivaroxaban, Dabigatran, and Edoxaban groups. The difference in major bleeding was statistically significant (p = 0.03), whereas other outcomes showed favorable but non-significant trends. Hospitalization and mortality rates were comparable across groups (p > 0.05). Conclusion: This study suggests that Apixaban provides a safer profile with significantly lower major bleeding and a trend toward fewer thromboembolic events in obese AF patients. Apixaban may be preferred for anticoagulation in this population, although larger multicenter studies are warranted to validate these findings